Local Culture-Based Investment Decisions and Financial Well-Being Among Msmes: A Systematic Literature Review - Meriyana Fransisca Dungga; Mahludin Baruadi; Hais Dama; Tineke Wolok (Dinasti International Journal of Management Science, 2026)
Financial well-being has become a strategic concern in household finance, MSME development, and inclusive growth, especially in emerging economies where financial access often grows faster than financial capability. This study conducts a systematic literature review to examine how financial literacy, financial inclusion, financial experience, and financial behavior shape financial well-being through the mediating role of local culture-based investment decisions among micro, small, and medium-sized enterprises (MSMEs). Guided by a PRISMA-based review logic, this article integrates Behavioral Finance Theory, the Theory of Planned Behavior, and Socio-Cultural Theory to explain financial well-being as a culturally embedded outcome of knowledge, access, experience, behavior, and investment judgment. Based on 33 selected studies, the review identifies four dominant streams: financial capability and literacy, financial inclusion and digital access, behavioral finance and investment decision-making, and socio-cultural embeddedness in financial well-being. The synthesis shows that local culture-based investment decisions serve as a contextual bridge between modern financial systems and community-based economic values. This review contributes an integrative framework for future MSME research and offers practical implications for culturally grounded financial literacy, inclusive finance, and investment assistance programs.